An investigation on the impact of job motivation as a mediator between job satisfaction and employee loyalty: A case in Telekom Malaysia Berhad / Nabila Azfa Anuar - Anuar, Nabila Azfa (Bachelor of Science (Hons) Statistics, 2014)
Loyalty is a crucial issue in telecommunication industry. Information, communication and technology (ICT) sector have the highest annual average turnover rate and this issue is quite worrisome. This study was carried out to discover the relationship and influence of the determinants of job satisfaction such as work stress, role within organization, workplace wellbeing, workplace environment, role within organization and career development; and the impact of job motivation as a mediator between job satisfaction and employee loyalty. Simple random sampling (SRS) design was carried out, covering the Group Business and Customer Management (GBCM) staffs in Menara Telekom. The data were distributed to 232 respondents using self-structured questionnaires. The relationships of the variables were analyzed using Pearson’s Correlation. Simple linear regression was employed to examine the impact of emotional intelligence towards work stress, job satisfaction towards job motivation, and job motivation towards employee loyalty. On the other hand, multiple linear regressions were employed to measure the impact of several determinants toward job satisfaction. All paired variables have positive relationship with the related dependent variables. Besides that, all objectives are achieved but there are two variables (career development and role within organization) that turn out to be not giving any influence towards the job satisfaction. The job satisfaction gives a significant impact towards the job motivation while the job motivation has influence on the employee loyalty. Since both variables are related to job motivation, hence we can consider job motivation as a mediator between both job satisfaction and employee loyalty